A system for the management of old building retrofit projects in historical centres: the case of Portugal - Oliveira, Rui A. F.; Lopes, Jorge; Sousa, Hipólito; Abreu, Maria Isabel (International Journal of Strategic Property Management, 2017)
The retrofitting works in old buildings require appropriate knowledge of the vernacular techniques. Previous researches have identified retrofitting works as more intrusive and using more unnecessary demolition materials than real needs. This study constitutes a new framework that focuses on the project management success of old building retrofitting in historical centres by developing a methodological system for this purpose. It uses a construction sector system approach, reviews legal requirements, framework specifications, recommendation practices and sustainable measures adapted to old building projects. It presents 50 parameters adapted to these works’ specificities that could be used by construction market stakeholders. The research uses a case study methodology divided in two parts. The first one involves the review of building retrofitting projects in historical centres, complemented by a questionnaire in the second part. The results of the projects review have shown little concern with the underlying sustainability aspects of retrofitting works in all project designs analysed. However, the questionnaire results have revealed a high interest and applicability of all parameters omitted in the project designs data. The study describes a useful management system in a toolkit format which might contribute to reduce uncertainty in the management of retrofitting projects in historical centres.